2020
DOI: 10.5937/ekopolj2002585d
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural enterprises and economic growth: A regional analysis in the Republic of Serbia

Abstract: Since agriculture is the highly important economic activity in the Republic of Serbia, it is necessary to create an environment in which competitive agricultural enterprises will develop. However, regions in the Republic of Serbia considerably differ regarding the intensity of agricultural activity. This paper examines the impact of agricultural enterprises on the region's contribution to the gross domestic product (GDP) of the country in the period between 2010 and 2018. Activity of agricultural enterprises w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…A study by Dimitrijević, Vržina and Leković (2020) reported that Serbia is a mainly rural country, as three-quarters of its land makes rural areas, and about half of the residents are residing in these rural regions. Serbian farming is the segment that is very vital for the overall economy of the nation in respect of resources, contribution to the GDP and employment along with significance for rural regions and residents.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...mentioning
confidence: 99%
“…A study by Dimitrijević, Vržina and Leković (2020) reported that Serbia is a mainly rural country, as three-quarters of its land makes rural areas, and about half of the residents are residing in these rural regions. Serbian farming is the segment that is very vital for the overall economy of the nation in respect of resources, contribution to the GDP and employment along with significance for rural regions and residents.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...mentioning
confidence: 99%
“…It is also a well-known practice that some western countries have introduced credit quotas in order to force banks to direct loans in the interest of development. The largest number of employees in companies from the processing industry sector (14) evaluates the importance of the factor Sources of financing with a very good grade, while the largest number of employees in companies engaged in agriculture (10) evaluates this factor with a good and very good grade (Table 4). No statistically significant differences were found (χ2 = 2.473, p> 0.05) in the assessment of the factor Sources of financing with regard to the enterprise sector.…”
Section: Financing Sourcesmentioning
confidence: 99%
“…Good decisions are those that are based on timely and comprehensive information, obtained by applying appropriate criteria, that are made at the optimal time, and that are tested in terms of the sensitivity of the decision to the accuracy of the assumptions on which it is based. The largest number of employees from the processing industry (14) and agriculture (10) rate the Investment decisions' risk factor with a very good score (Table 6). No statistically significant differences were found (χ2 = 3.267, p> 0.05) in the assessment of the Risk of investment decisions factor with regard to the enterprise sector.…”
Section: Investment Decisions' Riskmentioning
confidence: 99%
“…The analysis of financial and economic indicators of agricultural production in the region, based on the analysis of industry enterprises, is of great importance both for government authorities that form investment and tax policy, and for potential investors and partners, as well as for the heads of companies. The method of integral estimates [1][2][3][4][5][6][7][8]11], which takes into account the relationship between various indicators of the enterprise, allows to track the possible dynamics of its development, currently is quite widespread. However, it has significant disadvantages associated with a subjective approach to determining expert assessments and does not take into account the specific (sectors) features of the enterprise [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For evaluating financial and economic state of a particular sectors in a particular region, there are techniques that are usually based on the analysis of some aggregate indicators and do not allow for analysis of financial and economic condition of the sector in the region based on performance of individual enterprise is taken from open internet sources. The purpose of this research is to develop and test a new methodology that allows performing financial and economic analysis of enterprises in a particular industry based on open Internet data sources, using classical methods of intellectual data mining (IDM) and a system of fuzzy logical conclusions [2,5,13]. To achieve this purpose, the following tasks have been set and solved.…”
Section: Introductionmentioning
confidence: 99%